Better the devil you know: common terns stay with a previous partner although pair bond duration does not affect breeding output - Fernando Colchero; Maren Rebke; Peter H. Becker (Proceedings of the Royal Society B: Biological Sciences, 2017)
In a monogamous species two partners contribute to the breeding process. We study pair formation as well as the effect of pair bond length and age on breeding performance, incorporating individual heterogeneity, based on a high-quality dataset of a long-lived seabird, the common tern ( Sterna hirundo ). To handle missing information and model the complicated processes driving reproduction, we use a hierarchical Bayesian model of the steps that lead to the number of fledglings, including processes at the individual and the pair level. The results show that the age of both partners is important for reproductive performance, with similar patterns for both sexes and individual heterogeneity in reproductive performance, but pair bond length is not. The terns are more likely to choose a former partner independent of the previous breeding outcome with that partner, which suggests a tendency to retain the partner chosen at the beginning of the breeding career.